Estudo da farinha e da goma de algaroba (Prosopis spp.) - Galán, Abel González (2009)
The algarroba (Propopis spp.), a Leguminous tree found in arid and semi-arid regions of Bolivia and Brazil, is underused, mainly due to lack of knowledge of its chemical, physical and functional characteristics. The objective of this study was to determine the chemical composition of the fruit of different species of algarrobo from Bolivia and Brazil, to make muffins, and to characterize the gum in the flour and seed and its possible hypoglycemic effect. Functional characteristics of grain size, water and oil absorption, color, pH and acidity were determined. Proximal composition, amount of starch, sugars, minerals and in vitro protein digestibility were analyzed. The antinutritional factors studied were: saponin, hemagglutination activity, trypsin inhibitor, polyphenol, nitrate, oxalate and phytate. Algarroba (Prosopis alba) fruit flour (AFF) was added in formulating muffins aimed at increasing the proportion of dietary fiber and decreasing the concentration of sugar. Muffins were prepared with 0%, 10%, 20%, 30%, 40% and 50% of algarroba fruit flour. Texture profile analyses were conducted by dual compression or TPA (hardness, springiness and cohesiveness). An acceptance test and shopping intentions was carried out using a structure hedonic scale. To extract the gum from the AFF from P. juliflora a technique was selected which obtained the highest proportion of soluble fiber. Gum extracted from the seeds of P. alba was added in 25 and 50% above the proportion of soluble fiber in the diet control animal used in the experiment to verify the possible effect of this in diabetic mice. The fruit of algaroba produces flour with good capacity to absorb water and oil, absorbing water up to 2.55 times its own weight (P. alba). In the oil absorption of P. chilensis is highlighted. The color results indicate meal with clear characteristics of light, slight tendency to red and pronounced yellowing. Flour showed a good source of iron, potassium and phosphorus and deficient in calcium. The average levels of crude protein (10.05 g 100 g-1 dry mather - DM), ash (3.68 g 100 g-1 DM), ether extract (1.08 g 100 g-1 DM), dietary fiber (45, 13 g 100 g-1 DM), non-reducing sugars (ranging from 36.46 to 52.51 g 100 g-1 DM) and higher digestibility of P. juliflora (66.45%) were reported. P. juliflora showed the higher value of trypsin inhibitors 9.32 UTI mg-1 DM, was well inferior to that of raw soy. Regarding saponin, hemagglutinin and poliphenol, the levels found are considered low. As for nitrates, the levels found were higher than those reported for peas and beans, with P. chilensis presenting the highest value (2.92 g NO3- kg-1 DM). Muffins showed an increased in fiber concentration of 150% and a decrease in the caloric value of approximately 15% in the replacement of 50% of wheat flour by AFF showing a good acceptance. The method selected to extract was the one that used a proportion of 1:10 flour to water at 70oC for 60 minutes, reaching an extraction of 9.5%. The chemical characteristics indicate a gum with a higher purity to 78% and high protein concentration. The doses used gum (25% and 50% of soluble fiber on the value in the standard diet) showed the effect in control polyphagia of diabetic rats.